A new hermit crab (Decapoda: Anomura: Paguroidea: Paguridae) from the eastern North Pacific - Ng, Ngan Kee; Mclaughli, Patsy A. (Zootaxa, 2009)
A new intertidal species of the hermit crab genus Pagurus, recently discovered on the Olympic Peninsula of Washington, is described and illustrated. This species, Pagurus holmi n. sp., is compared and contrasted to other regional shallowwater species.